Using contractual incentives in district nursing in the English NHS: results from a qualitative study. Issue 3 (16th April 2018) - Petsoulas, Christina; Allen, Pauline; Horrocks, Susan; Pollard, Katherine; Duncan, Lorna; Gibbard, Emma; Wye, Lesley; McDonald, Ruth; Cook, Jane; Husband, Pete
Abstract : Since 2008, health policy in England has been focusing increasingly on improving quality in healthcare services. To ensure quality improvements in community nursing, providers are required to meet several quality targets, including an incentive scheme known as Commissioning for Quality and Innovation (CQUIN). This paper reports on a study of how financial incentives are used in district nursing, an area of care which is particularly difficult to measure and monitor.